SUSTAINABLE AGRICULTURE OF THE SMALL COCONUT FARMERS - Dr. D.V. Liyanage (International Coconut Community, 1990)
Coconut cultivation is generally a small‑holder enterprise. Production of nuts is low due to the various constraints faced by the farmers. Assuming that 20% of the area under cultivation in all the countries consist of non‑bearing palms and vacancies, the average production for the period 1984‑1988 was 4,900 nuts per hectare of bearing palms per year. If improved management practices arc carried out on the existing holdings, yield could be increased by at least 50 percent. But, they arc beyond the capacity of the farmers to implement.